Better postural control during accurate shooting in elite female basketball players - Wang Wang, Y. T.; Tseng, T. L.; Chi, L.; Huang, C. F.; Lin, P. C.; Lee, J. Y. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to evaluate the differences of postural control (PC) during accurate and inaccurate shooting in elite female basketball players. 21 female professional basketball players recruited as subjects. The PC was evaluated by the Accusway as sway radius, velocity, radial and 95% area of the center of pressure (COP) during standard penalty line shooting. The results showed that the COP sway area during accurate shooting was significantly smaller than during inaccurate shooting (74.0 ± 37.9 vs. 110.6 ± 49.1, p < .05). Moreover, no significant differences were found between situations in the COP radius and velocity. This study found that during the accurate shooting, elite female basketball player had better PC which demonstrated that significant smaller COP sway area than inaccurate shooting.